The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cells10092354
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Polymorphism of the Subchloroplast—Granum and Stroma Thylakoid Membrane—Particles. I. 31P-NMR Spectroscopy

Abstract: Build-up of the energized state of thylakoid membranes and the synthesis of ATP are warranted by organizing their bulk lipids into a bilayer. However, the major lipid species of these membranes, monogalactosyldiacylglycerol, is a non-bilayer lipid. It has also been documented that fully functional thylakoid membranes, in addition to the bilayer, contain an inverted hexagonal (HII) phase and two isotropic phases. To shed light on the origin of these non-lamellar phases, we performed 31P-NMR spectroscopy experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The addition of 20 U mL −1 WGL further suppressed the isotropic phases and diminished the L and H II phases; at 100 U mL −1 of WGL, all phases were eliminated ( Figure 6 ). These data are in good agreement with our previous results on isolated granum and stroma sub-chloroplast TM particles [ 38 , 39 ]. It is important to note that 5 U mL −1 WGL, even over long incubation times, did not disturb the structure and function of TMs; it did not increase the permeability of the membranes and exerted no effects on the excitation-energy distribution in the TMs, on the activity of PSII, nor the pattern and macro-organization of PPCs ( Figure S4 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The addition of 20 U mL −1 WGL further suppressed the isotropic phases and diminished the L and H II phases; at 100 U mL −1 of WGL, all phases were eliminated ( Figure 6 ). These data are in good agreement with our previous results on isolated granum and stroma sub-chloroplast TM particles [ 38 , 39 ]. It is important to note that 5 U mL −1 WGL, even over long incubation times, did not disturb the structure and function of TMs; it did not increase the permeability of the membranes and exerted no effects on the excitation-energy distribution in the TMs, on the activity of PSII, nor the pattern and macro-organization of PPCs ( Figure S4 ).…”
Section: Resultssupporting
confidence: 93%
“…The large amplitude of the 31 P-NMR band arising from the lipid phase with inverted hexagonal geometry showed that this phase, in intact TMs, contained large amounts of lipids (~40% of the detectable bulk lipids—see Figure S1b ). However, as previously tested on granum and stroma TM fractions [ 38 ] and on intact TMs (unpublished data), they did not adopt long-range order structures.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies showed that the main lipid component of the thylakoid layer structure such as monogalactosyldiacylglycerol (MGDG), digalactosyldiacylglycerol (DGDG), phosphatidylglycerol (PG) and sulfoquinovosyldiacylglycerol (SQDG) [ 2 , 35 , 36 ]. Therefore, we used thin-layer chromatography to analyze the lipid content in leaves.…”
Section: Resultsmentioning
confidence: 99%